Polycystic ovary syndrome and pregnancy - review - Grześk-Kaczyńska, Magdalena; Ostrowska, Magdalena; Pałac, Dominika; Kaczyński, Szymon (Journal of Education, Health and Sport, 2022)
Introduction and purpose Polycystic Ovary Syndrome(PCOS) is one of the most common endocrinological disorders, and it affects 7-8 % of women globally. It is very heterogenous disease, which pathogenesis is complex and composed of many factors like genetics, hormonal changes, environmental factors and insulin resistance. PCOS has many symptoms, which appearance is dependent on comorbidities like obesity, diabetes mellitus, hypercholesterolemia. Due to complexity of the pathogenesis of PCOS it may have four phenotypes: A,B,C,D. The pregnancy pathologies connected to PCOS are mainly gestational diabetes mellitus, pregnancy induced hypertension. Pregnant women with PCOS have 3-4 times a higher risk of developing pregnancy induced hypertension (PIH) and preeclampsia and a three times higher risk of gestational diabetes mellitus (GDM). More than 64% of pregnancies in women with PCOS were terminated via caesarean section. Metformin, although still controversial may be a good option for the treatment of PCOS before and during pregnancy as a second-line therapy. PCOS is a disease which affects the women in childbearing age and may have negative impact on its course. Pathologies connected to PCOS during pregnancy affect not only mothers, but foetus and according to new researches also children and adults from mothers with PCOS. It is very essential to extract women with PCOS to implement treatment and prevent its complications. Moreover, due to its common association with obesity patients should be under cardiologists care due to higher cardiovascular risk.